Selective binding of pVTK peptide-and bisphosphonate-functionalized micelles to prostate cancer cells, osteoblasts, and osteoclasts - Aydın, Ömer; Tiruchinapally, Gopinath; Youssef, Ibrahim; Ramaraju, Harsha; Yüksel Durmaz, Yasemin; Kozloff, Kenneth M.; Kohn, David H.; Elsayed, Mohamed E. H. (Andover House, Inc., 2022)
This report describes the development of functionalized polymeric micelles encapsulating a chemotherapeutic agent. The results indicate the ability to achieve selective uptake into different cell populations in metastatic prostate cancer in vitro by appropriate selection of the targeting ligand. This paves the way for administering single or multiple therapeutic agents into bone metastases. These particles are functionalized to display the pVTK peptide of bisphosphonate (BP) as two different targeting ligands to assess their ability to trigger selective binding and internalization into prostate cancer cells, osteoblasts, osteoclasts, and macrophages in vitro. These bone-targeting particles (60-90 nm) bind to hydroxyapatite/bone powder with high affinity. Uptake of pVTK-and BP-conjugated particles into prostate cancer cells (PC-3 and C4-2B), MC3T3, RAW264.7 bone macrophages, and RANKL-activated RAW264.7 cells cultured on a regular tissue culture plate and bone-like surface was investigated. Results show that increasing the number of BP-targeting ligands displayed on particle surface shows 60-fold higher affinity to RAW 264.7 macrophages seeded on conventional tissue culture plates than non-conjugated particles. In addition, the uptake study results show that pVTK-functionalized particles were selectively internalized by C4-2B and MC3T3 osteoblast cells cultured on BLS, whereas BP-functionalized particles are selectively internalized by PC-3 and RAW264.7 macrophage cells cultured on BLS. Therefore, efficient and selective bone-conjugated therapies are needed to kill cancer cells and inhibit the crosstalk with other cells in the metastatic lesion, resulting in osteoblastic, osteolytic, or a mixed phenotype.
Keywords: Bisphosphonates; Bone-Targeting Particles; Cabazitaxel; pH-Sensitive Micelles; pVTK Peptide